Tumor-Derived cGAMP Regulates Activation of the Vasculature - Marco Campisi; Marco Campisi; Shriram K. Sundararaman; Shriram K. Sundararaman; Sarah E. Shelton; Sarah E. Shelton; Erik H. Knelson; Navin R. Mahadevan; Navin R. Mahadevan; Ryohei Yoshida; Tetsuo Tani; Elena Ivanova; et al. (Frontiers in Immunology, 2020)
Intratumoral recruitment of immune cells following innate immune activation is critical for anti-tumor immunity and involves cytosolic dsDNA sensing by the cGAS/STING pathway. We have previously shown that KRAS-LKB1 (KL) mutant lung cancer, which is resistant to PD-1 blockade, exhibits silencing of STING, impaired tumor cell production of immune chemoattractants, and T cell exclusion. Since the vasculature is also a critical gatekeeper of immune cell infiltration into tumors, we developed a novel microfluidic model to study KL tumor-vascular interactions. Notably, dsDNA priming of LKB1-reconstituted tumor cells activates the microvasculature, even when tumor cell STING is deleted. cGAS-driven extracellular export of 2′3′ cGAMP by cancer cells activates STING signaling in endothelial cells and cooperates with type 1 interferon to increase vascular permeability and expression of E selectin, VCAM-1, and ICAM-1 and T cell adhesion to the endothelium. Thus, tumor cell cGAS-STING signaling not only produces T cell chemoattractants, but also primes tumor vasculature for immune cell escape.